Pembuatan Kebun Rempah “Seruputan” sebagai Upaya Pengembangan Kampung Mompreneur bagi Warga Binaan PKK Putat Wetan - Nurul Dzakiya; Elisabeth Amanda E.F. Sari Lewoema; Rahma Laila Fitriah; Zhulfikar Esa Amirul Mu’minin; Ryand Martin Sinaga (Indonesian Journal of Community Empowerment and Service (ICOMES), 2021)
Mompreneur village, which is currently established under the guidance of the HMTG "GAIA" Village Development and Empowerment Program Team (P3D), has succeeded with the traditional drink product "seruputan" which has been able to be sold outside of Yogyakarta. However, the current problem is that the production of the product is constrained due to the lack of raw materials for the main spices. On the other hand, there are residents' land that has not been used. The purpose of this service is to increase the spice land by utilizing the land of residents who are not yet productive. As a result, the creation of a “sruputan” spice garden together with the assisted residents was achieved according to the target by planting various spices that sparked business ideas in innovating various flavors of 'sruputan' products and other forms of slurry products. Keywords: Spice Garden,  traditional drinks, village empowerment, putat wetan